Liver transplantation for hepatitis C virus related liver disease. Issue 962 (12th December 2005) - Gee, I; Alexander, G
Abstract : Liver transplantation is a useful treatment for end stage liver disease of all aetiologies but recurrent disease presents an ongoing challenge, particularly for hepatitis C virus (HCV) where recurrence is almost universal. Immunosuppression is needed for all patients after transplantation and should be tailored to the individual patient, with particular problems being noted for those with HCV. The longer term effects of immunosuppression, particularly renal failure and the adverse effects of certain treatments on the liver graft, have become more important as survival improves and results are studied for longer periods after transplantation.